Neurocysticercosis with symptomatic epilepsy manifestation - Nataliya Nekrasova; Olena Tovazhnyanska; Daryna Sushetska; Olena Markovska; Anton Shapkin; Rhea Singh; Yevhenija Soloviova; Dmytro Butov (Medicinski glasnik, 2021)
Aim: To present a unique case of a 22-year-old male patient with symptomatic epilepsy manifestation on a background of neurocysticercosis (NCC). Methods: An Indian student in Kharkiv, who lived in rural parts in India, presented with sudden episodes of seizure followed by severe headaches. Laboratory analyses and neurological status (MRI) were performed. Results: Neurological status of the patient revealed nystagmus and difficulty in performing coordination tests. General analysis of blood showed raised eosinophil count to 8%. The MRI showed a few small conglomerating peripherally enhancing thick-walled infective granulomas in left frontal lobe with extensive surrounding oedema in the left fronto-parietal lobe. The patient was treated with albendazol, levipil, methylprednisolone and pantoprazole. Clinical symptoms and subsequent MRI showed improvement. Conclusion: Neurocysticercosis is often misdiagnosed in the early stages, which leads to adverse outcomes. Although seizures are the most common clinical manifestation, it is a symptom that is not found in majority of the patients. The NCC of adult onset accompanying epileptic seizures is not well studied and a link between the helminthic invasion, epilepsy and psychiatric conditions needs to be established. This disease is potentially eradicable with wellplanned eradication programs targeting all stages of Taenia solium life cycle.
Keywords: granuloma; frontal lobe; seizures; Taenia solium